Evolutionary dynamics of retrotransposable elements Rex1, Rex3 and Rex6 in neotropical cichlid genomes - Schneider, Carlos Henrique (2020)
Background: Transposable elements (TEs) have the potential to produce broad changes in the genomes of their hosts, acting as a type of evolutionary toolbox and generating a collection of new regulatory and coding sequences. Several TE classes have been studied in Neotropical cichlids; however, the information gained from these studies is restricted to the physical chromosome mapping, whereas the genetic diversity of the TEs remains unknown. Therefore, the genomic organization of the non-LTR retrotransposons Rex1, Rex3, and Rex6 in five Amazonian cichlid species was evaluated using physical chromosome mapping and DNA sequencing to provide information about the role of TEs in the evolution of cichlid genomes. Results: Physical mapping revealed abundant TE clusters dispersed throughout the chromosomes. Furthermore, several species showed conspicuous clusters accumulation in the centromeric and terminal portions of the chromosomes. These TE chromosomal sites are associated with both heterochromatic and euchromatic regions. A higher number of Rex1 clusters were observed among the derived species. The Rex1 and Rex3 nucleotide sequences were more conserved in the basal species than in the derived species; however, this pattern was not observed in Rex6. In addition, it was possible to observe conserved blocks corresponding to the reverse transcriptase fragment of the Rex1 and Rex3 clones and to the endonuclease of Rex6. Conclusion: Our data showed no congruence between the Bayesian trees generated for Rex1, Rex3 and Rex6 of cichlid species and phylogenetic hypothesis described for the group. Rex1 and Rex3 nucleotide sequences were more conserved in the basal species whereas Rex6 exhibited high substitution rates in both basal and derived species. The distribution of Rex elements in cichlid genomes suggests that such elements are under the action of evolutionary mechanisms that lead to their accumulation in particular chromosome regions, mostly in heterochromatins. © 2013 Schneider et al.; licensee BioMed Central Ltd.